A sociocultural study on emotionality and Cognition as features of teacher knowledge and Practice - Encinas Sanchez, Mabel (Revista Enfoques Educacionales, 2017)
Although acknowledged, emotions have been consistently bracketed out of research on teacher training (Goodson, 1992; Day, 1993; Cochran-Smith and Lytle, 1999), and sociocultural approaches (Lave and Wenger, 1991; Lave and Chaiklin, 1993; Salomon, 1993). Emotions have been considered as independent of social practices, reducing them to a subjective perspective (Hargreaves, 2000, 2002a, 2002b). However, emotions have recently been studied in sociology (Williams and Bendelow, 1998), particularly through the concept of emotional labour (Hochschild, 1983). These perspectives emphasize the social construction of emotionality, but they leave the complexities of individual participation in the context aside. By contrast, through the construction of an immanent, non-Cartesian, psychology derived from Vygotsky’s (1999) work, space is created for an account of emotionality in individual teacher practices and its role in teacher knowledge. This ethnographic case study involved an intervention in a Mexican urban secondary school (junior high school). The work was developed with four experienced teachers and it was during the analysis of the video and audio recordings and notes, that emotions within socialrelationships in the classroom were unveiled as an important part of teacher practice and knowledge.